Oxidation of Fe-2.25Cr-1Mo in presence of KCl(s) at 400 °C – Crack formation and its influence on oxidation kinetics. (February 2020) - Persdotter, A.; Sattari, M.; Larsson, E.; Olivas Ogaz, M.A.; Liske, J.; Jonsson, T.
Graphical abstract: Highlights: KCl accelerates corrosion of the low alloyed steel Fe-2.25Cr-1Mo and changes the oxide microstructure markedly at 400 °C. KCl reduces cohesion of the oxide scale formed on Fe-2.25Cr-1Mo and makes the oxide scale susceptible to crack formation. Delamination in combination with local cracks results in a global change in oxidation kinetics. Presence of KCl is proposed to lower the activation energy for diffusion in bulk and/or grain boundaries resulting in an increased diffusion rate. Abstract: Accelerated corrosion of boiler equipment remains a challenge for efficiently utilising biomass- and waste for power production. To overcome this challenge a better understanding of the influence of corrosive species present is required. This study focuses on the influence of KCl(s) on corrosion of Fe-2.25Cr-1Mo at 400 °C. This is done by well-controlled laboratory exposures and detailed microstructural investigation with ion and electron microscopy (TEM, FIB, SEM, EDX, XRD, TKD). The scale microstructures are linked to oxidation kinetics. The results indicate that KCl(s) increases the ionic diffusion through the oxide scale as well as introduces cracks and delamination resulting in a rapid periodic growth process.